Development of a novel intelligent laparoscope system for semi‐automatic minimally invasive surgery. Issue 1 (15th December 2019) - Sun, Yanwen; Pan, Bo; Fu, Yili; Cao, Fayi
Abstract: Background: Intelligent surgical robot has great significance to alleviate the fatigue of surgeons. In the minimally invasive surgery robot system, adding intelligent control method to the laparoscope control has great realizability and significance. Methods: Depth independent image Jacobian matrix was modified to make it suitable for laparoscope trocar constraint. We propose a method for intelligent and autonomous adjustment of surgeon's surgical field of view, enabling it to track and predict the motion trajectory of surgical instruments. Results: The result of experiment shows that the proposed method could realize tracking the surgical instruments and adjusting the surgical field of view autonomously. In case of occlusion, motion trajectory of surgical instruments can be predicted. Conclusion: The intelligent laparoscope system could improve the intelligent level of surgical robot system. Given providing "a third hand" for the surgeon, the proposed system is a highly improvement for semi‐autonomous surgical robot system.